Melalui Gerakan Nasional Revolusi Mental (GNRM) Perkokoh dan Bangun Karakter Bangsa dalam Menyongsong dan Menyukseskan PEMILU dan PILKADA Serentak Tahun 2024 di Kabupaten Bener Meriah - Iskandar Iskandar; Zainal Abidin; Murthada Murthada; Budiman Budiman; Seri Mughni Sulubara; Ranti Maulya; Sulistio Ningsih; Desi Purnama Sari; Amrizal Amrizal (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
First-time voters are first-time citizens. This group of first-time voters is usually those who are students as well as young workers. Novice voter participants do not have experience in participating in simultaneous elections and regional elections in 2024. First-time voters should be educated on how to vote correctly in accordance with the National Movement for Mental Revolution (GNRM). The problem in this research is how do novice voters, especially SMA/SMK/MA equivalent students in Bener Meriah Regency, welcome and succeed the 2024 ELECTIONS and SIMULTANEOUS ELECTIONS through the National Movement for Mental Revolution (GNRM). The purpose of this study was to find out how novice voter participants, especially SMA/SMK/MA equivalent students in Bener Meriah Regency, welcome and succeed the 2024 ELECTIONS and SIMULTANEOUS ELECTIONS through the National Movement for Mental Revolution (GNRM). The method used is a survey method to identify and analyze problems related to the level of ability, understanding and knowledge of SMA/SMK/MA equivalent students in Bener Meriah Regency and another method used is political literacy education for these students through community service activities This. The results of his research are that ELECTIONS and PILKADA simultaneously in 2024, especially in the Bener Meriah Regency area, can be carried out successfully and successfully by SMA/SMK/MA equivalent students in Bener Meriah Regency if they realize the five GNRM programs, namely the Indonesia Serving Movement, the Indonesian Movement Clean, Orderly Indonesia Movement, Independent Indonesia Movement, and United Indonesia Movement.